Adsorption of 4,4″-Diamino-p-Terphenyl on Cu(001): A First-Principles Study - Chang-Tian Wang; Yan-Fang Zhang; Shixuan Du (Surfaces, 2021)
Single-molecular devices show remarkable potential for applications in downscale electronic devices. The adsorption behavior of a molecule on a metal surface is of great importance from both fundamental and technological points of view. Herein, based on first-principles calculations, the adsorption of a 4,4″-diamino-p-terphenyl (DAT) molecule on a Cu(001) surface has been systematically explored. The most stable configuration is the DAT molecule lying flat with a rotation angle of 13° relative to the [100] surface direction. It was found that the adsorption sites of benzene rings and nitrogen atoms in the DAT molecule have important influences on the stability of the adsorption configuration. Electron density differences analysis shows that the electrons accumulate at the DAT-Cu(001) interface. The density of states projected on a DAT molecule of DAT/Cu(001) exhibits a metallic character, while the freestanding ones are semiconducting, indicating a strong interaction between the DAT molecule and the Cu(001) surface in the most stable adsorption configuration. These results provide useful information for tuning the properties and functions of DAT molecules, and may offer useful insights for other organic molecule/surface systems.